Prominin-1 (CD133): New Insights on Stem & Cancer Stem Cell Biology - Corbeil, Denis.; Corbeil, Denis. (Advances in Experimental Medicine and Biology,, 2013)
Since its first description fifteen years ago as a novel antigen of neural and hematopoietic stem cells, prominin-1 (alias CD133) has emerged concomitantly with stem and cancer stem cell research as an essential cell surface marker allowing identification and isolation of cells with stem cell properties. Although the physiological function of prominin-1 and the other members of prominin family remains elusive, its study has revealed new biological features regarding stem cells, cancer stem cells and photoreceptors. The latter cell type is illustrated by the association of mutations in prominin-1 (PROM1) gene with retinal degenerations including Stargardt-like macular dystrophy and retinitis pigmentosa. This book discusses these issues with contributions from leading experts in molecular and cellular biology, stem cells and tissue engineering. It also covers the potential role of prominin-1–positive stem cells in regenerative medicine, and its use as a biomarker of cancers originating from various organ systems and/or molecular target in cancer stem cell therapy. This book is an essential concise guide to the latest discoveries on prominin-1 and the applications in various medical research fields such as stem and cancer stem cells.   Denis Corbeil holds a PhD in Biochemistry (University of Montreal, Canada). He is head of Tissue Engineering Laboratories, Biotechnological Centre (BIOTEC), Technische Universität Dresden, Dresden, Germany.